Chemical Composition of Carbonate Hardground Cements as Reconstructive Tools for Phanerozoic Pore Fluids - Andrea M. Erhardt; Alexandra V. Turchyn; J. A. D. Dickson; Aleksey Y. Sadekov; Paul D. Taylor; Mark A. Wilson; Peter Scott; Daniel P. Schrag (Geochemistry, Geophysics, Geosystems, 2020)
Abstract In this study, we report the chemical composition of early carbonate cement precipitates in carbonate hardgrounds to understand the geochemical signature of near‐surface carbonate mineral precipitation. As carbonate hardgrounds lithify at or near the sediment‐water interface, they acquire cements that may be minimally evolved from paleoseawater. Using a suite of chemical measurements, we explore the potential of carbonate hardground cements as paleoenvironmental proxies. Trace metal and isotopic ratios, including some rare earth elements, Mg/Ca, manganese, and strontium concentrations, δ18O, δ13C, and 87Sr/86Sr, were analyzed in the carbonate cements from 17 Phanerozoic carbonate hardgrounds. The sensitivity of the geochemical signal to alteration depends on the geochemical analysis in question and the environmental water‐rock ratio. Of these samples, only our modern sample has measurements consistent with primary precipitation from seawater; all other samples precipitated from chemically evolved seawater or were influenced by meteoric water, even if only minimally changed. The more recent samples from the Cenozoic had seawater 87Sr/86Sr. The Mesozoic samples, in contrast, did not preserve seawater 87Sr/86Sr, even though the Mg/Ca, δ18O, and δ13C values were consistent with precipitation from seawater. Finally, the Paleozoic samples preserved expected seawater 87Sr/86Sr, though rare earth element and δ18O suggest primary precipitation was from evolved seawater. Additionally, we place our results in the context of open versus closed system precipitation using transects of the Mg/Ca ratios across individual cements. Overall, we stress that one geochemical measurement provides only a partial record of fluid composition, but multiple measurements allow a potential understanding of the seawater geochemical signal.